Wage-Employment Bargaining in a Unionized Oligopoly and International Market Integration - Nicole Gürtzgen (Universität Rostock, Institut für Volkswirtschaftslehre, 1998)
In a framework of a n-union/n-firm oligopoly, this paper analyzes the incentive for firms and unions to adopt efficient bargaining, i.e. negotiating over wages together with employment. The analysis is conducted for the case of autarchy and for an integrated product market. Firm profits, union utility and industry rents are compared under two different bargaining regimes - the right-to-manage model and the efficient bargaining model. For centralized negotiations, it is shown that under autarchy bargaining over wages and employment does not necessarily imply efficiency as total industry rents decrease. In the case of an integrated product market, however, adopting efficient bargaining raises rents if the market share of the domestic industry is relatively small.
Keywords: J50; L13; 330; Trade Unions; Oligopoly; Efficient Bargaining; Integration; Lohnverhandlungstheorie; Beschäftigung; Arbeitsnachfrage; Oligopol; Wirtschaftsintegration; Wirtschaftsunion; Theorie